Analysis of influencing factors of early neurological improvement after intravenous rt-PA thrombolysis in acute anterior circulation ischemic stroke - Xiufu, Zhang; Ruipeng, Liang; Jun, Zhou; Yonglong, Li; Yulin, Wang; Jian, Zeng; Xianglin, Chen; Lan, Shen; Zuowen, Zhang (Frontiers in Neurology, 2022)
Background and objective It has been widely reported that Early neurological improvement (ENI) after rt-PA intravenous thrombolysis contributes to a good long-term prognosis in patients experiencing acute ischemic stroke (AIS). However, which clinical factors influence after intravenous administration of recombinant tissue-type plasminogen activator (IV-rt PA) in AIS patients ENI is still unclear. This study aimed to evaluate the impact of influencing factors on the benefit of ENI after intravenous thrombolysis neurological improvement after IV-rt PA. Methods The data of 73 patients with acute anterior circulation ischemic stroke who received intravenous thrombolysis with rt-PA in Chongqing University Jiangjin Hospital from January 2021 to July 2022 were retrospectively studied. According to the change rate of 24 h NISHH score, the research subjects were divided into the recovery group, the significant curative effect group, the curative effect group and the no curative effect group, the ENI after intravenous thrombolysis with rt-PA was defined as the improvement rate of National Institutes of Health Stroke Scale (NIHSS)score >46% at 24 h after IV-rt PA, and univariate factor analysis was used Clinical factors associated with ENI after intravenous thrombolysis. Results According to the 24-h NIHSS improvement rate of rt-PA intravenous thrombolysis in patients with acute anterior circulation ischemic stroke, 35 cases (47.95%) of the study population had ENI. There was no statistical difference between the improvement and non-improvement group in general demographic data, stroke TOAST classification, stroke risk factors (history of stroke, heart disease, hyperlipidemia, hypertension), and laboratory test data. There was a statistically significant difference in the random blood glucose levels between the two groups (p < 0.001, t = 3.511). Conclusion The effect of rt-PA intravenous thrombolysis within the time window of patients with acute anterior circulation ischemic stroke is significant, but the ENI after thrombolysis is easily affected by the level of blood glucose; diabetes is the most important factor affecting the acute anterior circulation ischemic stroke patients Clinical factors of ENI after intravenous thrombolysis with rt-PA.